Perception and Understanding of Chemistry Teachers toward Digital Literacy Based on Teachers’ Competence in the Disruption Era - Bahriah, Eka Sapinatul; Yunita, Luki; Sholihat, Rizqy Nur (FKIP Universitas Lampung, 2022)
Digital literacy skills in the era of disruption are needed not only the ability to find, use and disseminate information in learning, but also the ability to make information, critical evaluation, accuracy of the application used and in-depth understanding of the content of the information so as not to cause errors. This study aims to describe the perception and understanding of digital literacy of chemistry teachers at the SMA/MA level in the era of disruption. The method used is descriptive method. The research sample was 23 high school/MA chemistry teachers in the Bogor area who were determined by cluster random sampling. The instruments used consisted of FGD instruments and questionnaires. The data obtained were analyzed descriptively quantitatively. Based on the data, it is known that the perception and understanding of high school/MA chemistry teachers on digital literacy in the era of disruption in the realm of educator competence is 86.40% (Very Good). The results of statistical tests state that there is no significant relationship between years of service, gender, school where they teach, and certification status with the digital literacy competence of chemistry teachers.Keywords: digital literacy, teacher perception, chemistry teacher.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp304-315